The Importance of Interpersonal Skills For Project Manager: Systematic Literature Review - Lathifah, Ari; Fadhilah, Jihan; Fitroh, Fitroh (Jurnal Manajemen Teknologi, 2024)
Abstract. Project management skills can significantly impact the outcomes of many business initiatives, particularly in project-oriented industries. While technical expertise is crucial, project managers also rely heavily on interpersonal skills to effectively lead teams and communicate with stakeholders. This study examines how project managers' interpersonal skills contribute to project success. Employing the Systematic Literature Review methodology, our focus was on identifying pertinent articles from Scopus. Our initial search using the 'Publish or Perish' software returned 42 articles. We then carefully evaluated each one, focusing on how well they contributed to our understanding of interpersonal skills in project management. This thorough review process allowed us to select the most relevant and insightful articles for our study. Keyword analysis revealed robust associations between ‘interpersonal skills’ and ‘project managers’, extending to key terms such as ‘project management’, ‘emotional intelligence’, ‘project success’, ‘leadership’, ‘information technology’, ‘construction’, ‘implementation’, ‘evaluation’, and ‘qualitative’. Building on these keyword relationships, our findings underscore the need for balanced skill development in practice and highlight opportunities for future research on measuring and developing interpersonal skills across diverse project contexts, emerging methodologies, and virtual team dynamics, aiming to bridge the gap between academic research and practical application in project management.  Keywords:  Interpersonal skill, project, project manager, project management, systematic literature review   Abstrak. Keterampilan manajemen proyek dapat berdampak signifikan terhadap hasil dari banyak inisiatif bisnis, khususnya dalam industri yang berorientasi pada proyek. Meskipun keahlian teknis sangat penting, manajer proyek juga sangat bergantung pada keterampilan interpersonal untuk memimpin tim dan berkomunikasi dengan para pemangku kepentingan secara efektif. Studi ini meneliti bagaimana keterampilan interpersonal manajer proyek berkontribusi terhadap keberhasilan proyek. Dengan menggunakan metodologi Tinjauan Literatur Sistematis, fokus kami adalah mengidentifikasi artikel-artikel terkait dari Scopus. Pencarian awal kami menggunakan perangkat lunak 'Publish or Perish' menghasilkan 42 artikel. Kami kemudian mengevaluasi masing-masing artikel dengan cermat, dengan fokus pada seberapa baik kontribusinya terhadap pemahaman kami tentang keterampilan interpersonal dalam manajemen proyek. Proses peninjauan menyeluruh ini memungkinkan kami untuk memilih artikel yang paling relevan dan berwawasan untuk studi kami. Analisis kata kunci mengungkapkan hubungan yang kuat antara 'keterampilan interpersonal' dan 'manajer proyek', yang meluas ke istilah-istilah utama seperti 'manajemen proyek', 'kecerdasan emosional', 'keberhasilan proyek', 'kepemimpinan', 'teknologi informasi', 'konstruksi', 'implementasi', 'evaluasi', dan 'kualitatif'. Berdasarkan hubungan kata kunci ini, temuan kami menggarisbawahi perlunya pengembangan keterampilan yang seimbang dalam praktik dan menyoroti peluang untuk penelitian di masa mendatang tentang pengukuran dan pengembangan keterampilan interpersonal di berbagai konteks proyek, metodologi yang muncul, dan dinamika tim virtual, yang bertujuan untuk menjembatani kesenjangan antara penelitian akademis dan aplikasi praktis dalam manajemen proyek.  Kata kunci: Keterampilan interpersonal, proyek, manajer proyek, manajemen proyek, tinjauan pustaka sistematis